Direct determination of monolayer MoS2 and WSe2 exciton binding energies on insulating and metallic substrates. (11th January 2018) - Park, Soohyung; Mutz, Niklas; Schultz, Thorsten; Blumstengel, Sylke; Han, Ali; Aljarb, Areej; Li, Lain-Jong; List-Kratochvil, Emil J W; Amsalem, Patrick; Koch, Norbert
Abstract: Understanding the excitonic nature of excited states in two-dimensional (2D) transition-metal dichalcogenides (TMDCs) is of key importance to make use of their optical and charge transport properties in optoelectronic applications. We contribute to this by the direct experimental determination of the exciton binding energy ( E b, exc ) of monolayer MoS2 and WSe2 on two fundamentally different substrates, i.e. the insulator sapphire and the metal gold. By combining angle-resolved direct and inverse photoelectron spectroscopy we measure the electronic band gap ( E g ), and by reflectance measurements the optical excitonic band gap ( E exc ). The difference of these two energies is E b, exc . The values of E g and E b, exc are 2.11 eV and 240 meV for MoS2 on sapphire, and 1.89 eV and 240 meV for WSe2 on sapphire. On Au E b, exc is decreased to 90 meV and 140 meV for MoS2 and WSe2, respectively. The significant E b, exc reduction is primarily due to a reduction of E g resulting from enhanced screening by the metal, while E exc is barely decreased for the metal support. Energy level diagrams determined at the K-point of the 2D TMDCs Brillouin zone show that MoS2 has more p-type character on Au as compared to sapphire, while WSe2 appears close to intrinsic on both. These results demonstrate that the impact of the dielectric environment of 2D TMDCs is more pronounced for individual charge carriers than for a correlated electron–hole pair, i.e. the exciton. A proper dielectric surrounding design for such 2D semiconductors can therefore be used to facilitate superior optoelectronic device function.